PREFERENCE IN LANGUAGE LEARNING STRATEGIES (LLS) OF THE STUDENTS IN THE ENGLISH LANGUAGE EDUCATION DEPARTMENT AT THE UNIVERSITY OF MUHAMMADIYAH JEMBER - Taufik Hidayah (Universitas Mahaputra Muhammad Yamin, 2020)
The present study aims at investigating the patterns of language learning strategy use employed by the sixth semester students of English language education program at the University of Muhammadiyah Jember. To achieve this objective, Oxford’s Strategy Inventory of Language Learning (SILL) (1990) along with a background questionnaire (a modified version of Oxford’s background questionnaire) were administered to the participants. The findings indicate that the research participants use language learning strategies at a high rate (more than 60%), but with differences in type and frequency of the individual learning strategies. The students reported a high frequent use of metacognitive and cognitive strategies. Other types of language learning strategies are also used by the students, although the frequency is lower than the previous two strategies. Based on the findings of the present study, some pedagogical implication were suggested to encourage students to reflect on their own strengths and weaknesses in skills and content courses and self-regulate learning so as to make progress with teachers’ assistance. Keywords: language learning strategies (LLS); Strategy Inventory of Language Learning (SILL); memory strategies; cognitive strategies; metacognitive strategies; socio-affective strategies; compensation strategies.